KARAKTERISASI RESERVOAR MENGGUNAKAN METODE INVERSI SIMULTAN PADA LAPANGAN âALMULKâ, FORMASI TALANG AKAR CEKUNGAN SUMATERA SELATAN - , FATHUL MUBIN, Drs. Budi Eka Nurcahya, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Study of acoustic impedance inversion method has been known and utilized as a method in reservoir characterization, for lithology and fluid discrimination. This Acoustic Impedance inversion has a limitation in discriminating lithology and fluid effects, and it is often found in many cases where the porous sand and shalestone have a similar impedance value. Because of that reason, there is needs a new invention method that can discriminate lithology and fluid effect better. The simultaneous inversion method was used in this research, using angle stack data as the input and then it was inverted simultaneously together to produce P impedance, S impedance, and density. The P impedance and S impedance were derived to produce lambda-mu-rho which are sensitive to the presence of fluid. The results of the sensitivity analysis showed that parameter of P impedance, S impedance lambda-rho and mu-rho could define lithology differences and fluid properly. Map of inversion result show that P impedance, density, and lamda-rho are able to identify the zone of reservoir and fluid in the porous sand clearly. There were three prospect areas namely Prospects-A, prospect-B, and prospect-C in ALMULK field around FM-E1 and FM-E2 wells that spread to the west and the north. In this area, the inversion result was were indicated by low P Impedance, low density, low lambda-rho, high S Impedance and high mu-rho.